(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Different multivariate analysis techniques were used to classify 33 Brassica rapa L. genotypes. The genotypes were grouped into five clusters. Cluster I contained the maximum number of genotypes. Cluster III earned the highest cluster mean value for number of primary branches/plant, number of secondary branches/plant, number of siliquae/plant and seed yield/plant. Therefore, more emphasis can be given on cluster III for selecting genotypes as parents for the hybridization program. The highest intra-cluster distance (3.822) was found in cluster I and the lowest (0.000) in cluster V. The highest inter-cluster distance (15.705) was observed between clusters III and V showing wide diversity among the groups. Principal component analysis (PCA) showed that the first three principal components accounted for 99.38 % of the total variation observed. Analysis of the factor loading of the component character indicated that the characters number of siliquae/plant, plant height and days to maturity were found responsible for genetic divergence. The role of number of siliquae/plant in both the vectors was important components for genetic divergence in these materials. Among the possible 528 combinations, the highest inter-genotypic distance (1.5975) was observed between G-27 (BARI sarisha-9 x BARI sarisha-6 S-62) and G-31 (BARI sarisha-15). Considering group and inter-genotypic distance, cluster mean, contribution of different characters towards the total divergence and other agronomic performance the genotypes G- 19 (BARI sarisha-6 x TORI-7 S-48), G-20 (F6 x BARI sarisha-9 S-52), G-27 and G-30 (BARI sarisha-6 x TORI-7 S-37) from cluster III; G-26 (F6 x BARI sarisha-9 S-15) and G-31 from cluster IV and G-33 (BARI sarisha-6) from cluster V would be considered as better parents for future hybridization program. Bangladesh J. Agril. Res. 40(3): 421-433, September 2015